Pengaruh Human Relation, Kompetensi dan Komunikasi tehadap Kinerja Karyawan pada PT. Bank Nagari Cabang Utama Sumatera Barat (Lembaga Pengembangan Kinerja Dosen, 2025)
Employee performance is the quality and quantity results achieved by an employee in carrying out his duties according to the responsibilities given to him. Employee performance is the level of achievement or results of a person's work from the targets that must be achieved or the tasks that must be carried out according to their respective responsibilities within the specified time period. The purpose of this research is to determine the influence of human relations, competence and communication on employee performance of Bank Nagari Main Branch West Sumatra employees. Through a questionnaire method with a sample using a Yamane technique, there were 163 respondents who were sampled in this research. From the hypothesis testing that has been carried out, it can be concluded that human relations has a positive and significant effect on employee performance, competence has a positive and significant effect on employee performance and communication has a positive and significant effect on employee performance.